2022
DOI: 10.1021/acsapm.1c01853
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Thiol–yne “Click” Networks Based on Propargylated Lignin for Adhesive Resin Applications

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Overall, the bonded wood panels' dry and wet bonding strength showed their acceptable tensile shear strength, as specified by the GB/T 14732−2006 National standard (>0.7 MPa), 20 which shows the potential of the BNPF resins as wood adhesives.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Overall, the bonded wood panels' dry and wet bonding strength showed their acceptable tensile shear strength, as specified by the GB/T 14732−2006 National standard (>0.7 MPa), 20 which shows the potential of the BNPF resins as wood adhesives.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…In recent decades, numerous research studies have been reported on exploiting lignin as a phenol replacement in PF resin synthesis for wood adhesive applications. ,, In our prior work, we successfully used kraft lignin (Indulin AT from Ingevity) as a partial replacement for phenolic monomer synthesis of biobased Novolac PF (BNPF) resin for wood bonding. The work showed that synthesized lignin-based PF resin exhibited the highest adhesion strength compared to the standard Novolac PF resin (NPF) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenolformaldehyde resol adhesive which has nanosized lignin (LNP) and microlignin (LMP) is added together. 255 The nanolignin can be used to cure reactant due to the high concentration of phenylpropane units in the molecules. Overall shear strength is increased by its uniform distribution, absorption, and inhibited dimensional changes, as well as by enhanced LNP specific surface area and reactivity.…”
Section: Poly Butylene Adipate-co-terephthalate (Pbat)mentioning
confidence: 99%